Keefektifan Media Video Animasi Canva Terhadap Peningkatan Hasil Belajar Dasar Gambar Teknik Siswa SMK: Effectiveness of Canva‑Based Animated Video Media in Improving Vocational High School Students’ Learning Outcomes in Basic Technical Drawing - Dani Saputra; Shohihatur Rohman (Universitas Pendidikan Ganesha, 2026)
This study aims to determine whether Canva animated video media is effective in improving learning outcomes in basic technical drawing for 10th-grade Automotive Technology students at SMK Muhammadiyah 2 Semarang. The background underlying this study is students’ low understanding of technical drawing material and a learning process that is still dominated by lecture-based methods without the use of learning media. This study employs a quantitative approach using a quasi-experimental design with a one-group pretest-posttest design. The sample consists of 29 students from Class X TO 4. Data collection utilized a multiple-choice test that had been validated for both validity and reliability. The validity test results showed that 22 items were valid while 3 items were invalid; the Cronbach’s Alpha result was 0.893, indicating that the instrument was highly reliable. The research results showed an increase in the students’ average score from 70.34 initially to 84.7 on the post-test. Furthermore, the normality test results showed that the data were normally distributed, with significance values of 0.503 for the pre-test and 0.088 for the post-test. Additionally, the paired-sample t-test yielded a significance value of <0.001, indicating a significant difference between the pre-test and post-test results. Thus, the Canva-based animated video medium was proven effective in improving learning outcomes for the subject matter